Sex Trafficking of Women. Civil Society Activism Against Sexual Slavery Between the 19th and the Early 20th Century - Guiomar Merodio; Elena Duque (Historia Social y de la Educación, 2021)
The struggle against human traffickig is not unique to our time. Nowadays, social initiatives and policies are greatly influenced by civil society activism against sexual slavery that emerged between the 19th and the early 20th century. This article presents an analysis and selection of historical landmarks from that period that achieved social and political impact in different countries such as the United States of America, the United Kingdom and Spain. To do so we followed different strategies including the review of scientific literature and relevant academic historical databases, the examination of theoretical contributions from intellectuals, social reformers and feminist activists from that time, and we also searched for international and national legislation from the early 20th century. Findings show a) the influence of the transatlantic anti-slavery movement in the rise of the feminist movement; b) the evolution of the civil society struggle against sexual exploitation within the feminist movement; c) the arrival of the anti-sex trafficking movement in Spain; d) the political impact of early civil society organizations against sex trafficking in the articulation of policies at the beginning of the 20th century. To acknowledge these historical legacies can contribute to the development of current anti-sex trafficking initiatives.